Pengaruh Struktur Corporate Governance terhadap Financial Distress - Tri Bodroastuti (STIE Widya Manggala, 2009)
Theoritically, the better the corporate governance structure of the company, the better the company’s performance it gets, so avoided from financial distress. The first objective of this research was to examine the most influence variables of corporate governance structure on financial distress. The second objective was to confirm the past research. A hypothesis showed that corporate governance structure influenced financial distress. The variables as proxy for corporate governance structure used in this research were the number of board of directors, the number of commissioner, public ownership, the number of board of director out, institutional ownership, and directors ownership. The samples consisted of 19 companies listed in Indonesia Stock Exchange or by using 95 observations during 2003 until 2007 periods. Moreover, it is chosen by purposive sampling. The analysis was started with descriptive statistic. The statistic method which was used to test the research hypothesis was logistic regression. Two log likelihood, Cox and Snell R Square, and Hosmer and Lemeshow test, used to examine goodness of fit model. The analysis showed that two log likehood test, Cox and Snell R Squared test, and Hosmes Lemeshow test denoted which used in this research have goodness of fit. The result of research showed that variables of corporate governance structure that influenced financial distress were the number of board of directors and the number of commissioner, while the others not influenced.